Genotoxicity and mutagenicity of Rosmarinus officinalis (Labiatae) essential oil in mammalian cells in vivo - Maistro, Edson Luis [UNESP]; Mota, S. F.; Lima, E. B.; Bernardes, B. M.; Goulart, F. C. [UNESP] (Funpec-editora, 2010)
Rosmarinus officinalis (rosemary) oil is widely used by the cosmetic, food, and pharmaceutical industries as a fragrance component of soaps, creams, lotions, and perfumes. Although it is popular, potential harmful side-effects of the oil have been described. We investigated the genotoxic and mutagenic potential of essential oil of R. officinalis in rodents, using comet, micronucleus and chromosome aberration assays. The animals were treated by gavage with one of three dosages of rosemary oil (300, 1000 or 2000 mg/kg). Liver and peripheral blood cells were collected from Swiss mice 24 h after treatment for the comet assay (genotoxicity endpoint), along with bone marrow cells for the micronucleus test (mutagenicity endpoint). Bone marrow cells were collected from Wistar rats 24 h after oil treatment for the micronucleus and chromosome aberration assays. Based on the comet assay, all three doses of rosemary oil induced significant increases in DNA damage in the mouse cells. There was a significant increase in micronucleated cells and chromosome aberrations only at the two higher doses. We conclude that rosemary essential oil provokes genotoxic and mutagenic effects when administered orally.
Keywords: Chromosome aberrations; Comet assay; Essential oil; Micronucleus test; Rosmarinus officinalis